Characterization of a Dibenzofuran-degrading strain of Pseudomonas aeruginosa, FA-HZ1. (July 2019) - Ali, Fawad; Hu, Haiyang; Wang, Weiwei; Zhou, Zikang; Shah, Syed Bilal; Xu, Ping; Tang, Hongzhi
Abstract: Dibenzofuran (DBF) derivatives have caused serious environmental problems, especially those produced by paper pulp bleaching and incineration processes. Prominent for its resilient mutagenicity and toxicity, DBF poses a major challenge to human health. In the present study, a new strain of Pseudomonas aeruginosa, FA-HZ1, with high DBF-degrading activity was isolated and identified. The determined optimum conditions for cell growth of strain FA-HZ1 were a temperature of 30 °C, pH 5.0, rotation rate of 200 rpm and 0.1 mM DBF as a carbon source. The biochemical and physiological features as well as usage of different carbon sources by FA-HZ1 were studied. The new strain was positive for arginine double hydrolase, gelatinase and citric acid, while it was negative for urease and lysine decarboxylase. It could utilize citric acid as its sole carbon source, but was negative for indole and H2 S production. Intermediates of DBF 1, 2-dihydroxy-1, 2-dihydrodibenzofuran, 1, 2-dihydroxydibenzofuran, 2-hydroxy-4-(3′-oxo-3′ H -benzofuran-2′-yliden)but-2-enoic acid, 2, 3-dihydroxybenzofuran, 2-oxo-2-(2′-hydrophenyl)lactic acid, and 2-hydroxy-2-(2′-hydroxyphenyl)acetic acid were detected and identified through liquid chromatography-mass analyses. FA-HZ1 metabolizes DBF by both the angular and lateral dioxygenation pathways. The genomic study identified 158 genes that were involved in the catabolism of aromatic compounds. To identify the key genes responsible for DBF degradation, a proteomic study was performed. A total of 1459 proteins were identified in strain FA-HZ1, of which 100 were up-regulated and 104 were down-regulated. A novel enzyme "HZ6359 dioxygenase", was amplified and expressed in pET-28a in E. coli BL21(DE3). The recombinant plasmid was successfully constructed, and was used for further experiments to verify its function. In addition, the strain FA-HZ1 can also degrade halogenated analogues such as 2, 8-dibromo dibenzofuran and 4-(4-bromophenyl) dibenzofuran. Undoubtedly, the isolation and characterization of new strain and the designed pathways is significant, as it could lead to the development of cost-effective and alternative remediation strategies. The degradation pathway of DBF by P. aeruginosa FA-HZ1 is a promising tool of biotechnological and environmental significance. Graphical abstract: Image 1 Highlights: A new DBF degrading strain Pseudomonas aeuginosa FA-HZ1, was isolated from the waste water. The optimal growth conditions for strain FA-HZ1 are 30 °C, pH 5.0, and 200 rpm min −1 with 0.1 mM DBF. The physiological and biochemical characteristics of the strain were determined. Several biodegradation intermediates were identified and a pathway for DBF degradation was proposed. A novel enzyme "HZ6359 dioxygenase", can transform DBF into 1, 2-dihydroxy-1, 2-dihydrodibenzofuran. Abstract : In the present study, a new strain of P. aeruginosa, FA-HZ1, which has the ability to use DBF as a carbon source, was isolated and characterized. The strain's physiological and biochemical features were studied. Intermediates were identified and a pathway for DBF degradation was proposed.